THE IMPACT OF E-SBN IMPLEMENTATION TOWARDS RETAIL GOVERNMENT BOND INVESTMENT - Fajri R Muhammad; Khumairah (Jurnal Manajemen dan Bisnis Performa, 2024)
Since May 2018, the Government of the Republic of Indonesia presents Retail Government Securities (SBN) as one of the investment instruments whose ordering system has changed to an electronic system "e-SBN". This system change is expected to affect the level of subscription and reach more investors. This study examines how the impact of this e-SBN system change on investment in Government Securities consisting of analyzing factors that affect investment in Retail SBN and comparing the level of subscription before and after the system change. The method used is quantitative method with panel data regression analysis technique, t-test and descriptive statistics. The results show that the number of distribution partners and the amount of spread have a significant effect on the total issuance of e-SBN. Then there are differences in the level of retailing and the number of investors that increased after the implementation the e-SBN.